The Effect of Acupressure on Increasing Oxygen Saturation in Pneumonia Patients - Mauliku, Novie Elvinawaty; Yudistira, Andy; Rumahorbo, Hotma; Inayah, Iin; Susilawati, Susilawati (Poltekkes Kemenkes Palu, 2024)
Pneumonia is one of the top 10 hospital admissions, with a case proportion of 53.95% male and 46.05% female. Pneumonia can cause complications in the oxygenation process that lead to decrease the oxygen saturation value and causes hypoxemia. The puspose of this study was to analyze the effectiveness of acupressure on increasing oxygen saturation in patients with pneumonia. The design used quasi experiment pre test and post test with control group design approach. The sampel of this study was patiens with pneumonia between of 18 to 64 years, which choosing by convenience sampling. Participants in the experimenal group received auricular acupressure at the Shen Men and 5 meridian points, that is LU1, LU2, BL11, BL 12, and BL13. Data collection was done by measuring oxygen saturation using a plus oxymeter. The analysis test to determine the effect of acupressure on oxygen saturation using the Mann-Whitney Test with a significance level of 0.05, and N-Gain. The results showed that average oxygen saturation before acupressure in the intervention group was 74.00% and in the control group 73.15%. After acupressure there was an increase of saturation oxygen 23,8% in the intervention group and 21% in the control, and the effect test showed that there was an effect of acupressure on oxygen saturation (pValue 0.000). The conclusion is acupressure therapy can accelerate increaseing oxygen saturation in pneumonia patients. Therefore, it is recommended that besade addition standard therapy, pneumonia patients can also be given acupressure to accelerate healing.